2010
DOI: 10.3762/bjoc.6.141
|View full text |Cite
|
Sign up to set email alerts
|

Highly substituted benzannulated cyclooctanol derivatives by samarium diiodide-induced cyclizations

Abstract: SummaryA series of γ-oxo esters suitably substituted with various styrene subunits was subjected to samarium diiodide-induced 8-endo-trig cyclizations. Efficacy, regioselectivity and stereoselectivity of these reactions via samarium ketyls strongly depend on the substitution pattern of the attacked alkene moiety. The stereoselectivity of the protonation of the intermediate samariumorganyl is also influenced by the structural features of the substrates. This systematic study reveals that steric and electronic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 61 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…For our systematic studies on samarium diiodide promoted cyclizations leading to benzannulated medium-sized rings [ 1 4 ] we required starting materials such as alkenyl-substituted compounds B ( Scheme 1 ). Obvious precursors for B are aryl iodides A that smoothly undergo palladium-catalyzed coupling reactions to provide the desired products.…”
Section: Introductionmentioning
confidence: 99%
“…For our systematic studies on samarium diiodide promoted cyclizations leading to benzannulated medium-sized rings [ 1 4 ] we required starting materials such as alkenyl-substituted compounds B ( Scheme 1 ). Obvious precursors for B are aryl iodides A that smoothly undergo palladium-catalyzed coupling reactions to provide the desired products.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the radical 13 formed by Bu 3 SnH-mediated reduction of bromide 9 could engage in a spirocyclisation reaction to give isomer 14 that then fragments in what would be the second step of a radical-based Smiles rearrangement and thereby generating the nitrogen-stabilized primary radical 15 . This last species would then participate in an 8- endo-trig cyclization reaction to give the benzylic-type radical 16 that either aromatizes through loss of a hydrogen atom (to give benzofuran 10 ) or abstracts a hydrogen atom to afford the dihydrobenzofuran 11 .…”
mentioning
confidence: 99%
“…In 2009, Reissig reported a rare example of SmI 2 -mediated 7exo-trig cyclization in studies on forming benzannulated carbocycles (Scheme 63). 241 Although the authors initially set out to explore the scope of SmI 2 −HMPA−t-BuOH-promoted 8endo-trig cyclizations between ketones and terminal unactivated olefins (cf., 8-endo-trig cyclization reported by Molander, Scheme 62), 242,243 they found that substituting the olefin with another phenyl group led to 7-exo-trig cyclizations. The benzannulated products were formed in good yields and as single diastereoisomers.…”
Section: Cross-coupling Via Radical Intermediatesmentioning
confidence: 96%
“…The benzannulated products were formed in good yields and as single diastereoisomers. In contrast, the cross-coupling of aldehydes and ketones with terminal olefins resulted in efficient 8- endo -trig cyclizations to furnish tricyclic lactones and benzannulated cyclooctanols (Schemes and ). , The mechanism was proposed to involve an equilibrium between the ketyl radical anion and eight-membered benzylic radical, with an irreversible second reduction step (Scheme ).…”
Section: Cross-coupling Via Radical Intermediatesmentioning
confidence: 99%